Ciclo da taxa Selic, convenç\~oes e rigidez do custo fiscal da dívida mobiliária: O efeito da recomposiç\~ao das carteiras em mercado - Luís Carlos Garcia de Magalh\~aes; Beatriz Estulano Vieira; Kolaï Z. J. Yannick; Salvador Teixeira Werneck Vianna (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
The management of Brazil's public debt imposes a high fiscal cost due to the burden of interest payments. A key factor contributing to the substantial cost of servicing public debt, which hinders the balance of public accounts, is the structurally high nominal and real basic interest rates. The evidence presented here suggests the existence of cost asymmetries in the stock of Domestic Federal Public Securities Debt (DFPSD) throughout the Selic rate. The average cost of the DFPSD aligns with the Selic rate during its upward phase. However, in the downward phase, the gap between the Selic rate and the average cost of the DFPSD stock widens. Therefore, the asymmetry in fiscal costs throughout the Selic rate cycle can be explained, at least in part, by the institutional arrangement of public debt management, particularly the conventions that shape the behavior of private economic agents trading in DFPSD.
Keywords: E4; G1; H6; 330; Selic rate; DFPSD; TFB; NTB; NTN-B